Global South Perspective on the Threat to Multilateralism in G20 Post-Russia’s Invasion of Ukraine - Maudy Noor Fadhlia; Azza Bimantara (Institute of International Studies, 2022)
The G20 is set up to foster cooperation among states while sharing common principles and values. Even though it was first created to handle the global financial crisis, G20 has become a big multilateral forum covering other strategic developmental issues. At the beginning of this year, Russia's invasion of Ukraine came unexpectedly and created commotion among the G20 members. Some members assume it threatens multilateralism in G20 since Russia ignores international law. This paper uses a qualitative approach through a case study, collects the data from a literature review, and looks at different dimensions of multilateralism. Furthermore, the discussion will focus on the perspective of the Global South regarding the multilateralism crisis by overviewing the characteristics of multilateralism in crisis. The result of this paper indicates that the division among the West, Russia, China, and other members showed that the consensus and compliance in G20 no longer exist. It is considered a sign of the deficit of multilateralism where Russia and the West challenged and then pressured the multilateral system. On the other hand, most Global South countries took a different perspective and stance when the West and its allies heavily condemned Russia. While the other countries busily try to expel Russia from G20, the Global South representative countries remain neutral to maintain their relationship with the superpowers. The different perspectives and actions among the G20 members emphasize the crisis of multilateralism that reflects a battle of narratives.